Magical Iconography. How Can an Image Protect and Heal? - First, Grzegorz (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
One of the features of the attitude of ancient societies towards the threats of everyday life was a close relationship between spiritual/magical and religious beliefs and the real actions aimed at overcoming dangers. This relationship is visible in the magical iconography of Ancient Egypt and other Ancient Near Eastern cultures – in the form of demons, minor deities, and other benevolent supernatural beings that can protect people. Images of theses deities are sometimes accompanied by archaeological traces (holes for water, traces of rubbing, touching), indicating that images were also subjects of action. The question is how the magical and religious iconography meets the non-supernatural actions and how this custom could emerge in other parts of the Ancient world and in post-ancient times.